Quality of Life and Associated Factors Among Male Wheelchair Handball Athletes. Issue 4 (August 2021) - Calheiros, David dos Santos; Neto, Jorge Lopes Cavalcante; Melo, Flávio Anderson Pedrosa de; Pedrosa de Melo, Fábio Ítalo; Munster, Mey de Abreu van
Although scarce, some recent studies have observed good self-reported quality of life (QOL) among wheelchair users who are involved in adapted sports. These findings have encouraged further investigations, particularly investigations of combined sociodemographic and sport factors in the study of QOL. In this study we analyzed the association between sociodemographic and sport factors with QOL in a cross-sectional study of 105 male wheelchair handball (WH) athletes with higher and lower QOL. We used the World Health Organization Quality of Life – BREF (WHOQOL-BREF) scale to evaluate the respondents QOL; and we used a sociodemographic questionnaire to evaluate associated sociodemographic and sport factors. A logistic regression analysis found these athletes' good QOL to be generally characterized by stable marital status, disability due to cerebral palsy, the use of locomotion/mobility resources, full independence, bi-weekly training, and the use of a custom-made wheelchair for around 70% of their daily living activities. These findings support the role of such sociodemographic and sport factors in determining QOL among these WH respondents. These findings reveal the important issues to be considered in the sport modality when attempting to improve the QOL and functionality of these participants and perhaps WH athletes worldwide.